Self-calibration of RA-PKM via motion reverse points: A procedure based on an analytical indicator function. Issue 5 (3rd September 2019) - Ruggiu, Maurizio; Müller, Andreas
Abstract: A novel optimization algorithm for the calibration of redundantly actuated parallel manipulator (RA-PKM) is presented. The method uses an analytical indicator function (IF) which takes a specific value at the motion reversal points (MRP). MRP are configurations where the speed of one passive actuator vanishes during a continuous motion. IF depends on the passive actuator, the locked actuators, the geometrical parameters. The main idea is to perform an optmization that makes the IF equal to the specific value at the MRP whenever the geometrical parameters match the real values. Simulations of the calibration of a planar 4-RP R RA-PKM are presented. Communicated by S. Velinsky.